O curso técnico em administração integrado ao ensino médio do Centro Paula Souza: o processo de adequação à reforma do ensino médio e a base nacional comum curricular - Lima, Francisco de Assis Ferreira (2024)
The secondary education reform and the BNCC defined changes in Brazilian education in two fundamental axes: the change in course hours and the restructuring of the curricular organization. The research aimed to problematize how the curriculum proposed for the High School course with the professional qualification of Administration Technician at Centro Paula Souza (CPS) and how it incorporates these reforms. For this purpose, it used as a documentary reference the Course Plans prepared by the CPS in different periods, before and after the reform. The research also aimed to find out the perception that course teachers have regarding the changes that materialize in the course plans. The question that guided the research was the following: what changes occurred in the High School course with the professional qualification of Administration Technician at Centro Paula Sousa due to the 2017 high school reform and the 2018 BNCC? What is the perception of the teachers who work on the course about these changes? The general objective was to show what changes occurred in the Course Plans and what perception teachers have of these changes. The research, of a qualitative nature, used as sources the official documents of the MEC that deal with the reform of secondary education, the final document of the BNCC, opinions of the National Education Council and the State Education Council, pedagogical guidance documents produced for Schools Techniques from the Paula Sousa Center in São Paulo and organizational documents for the technical course in administration, specifically the Course Plans. Also sources of research are a set of semi-structured interviews carried out with course teachers, both from technical-based disciplines and from the BNCC. The documentary analysis we carried out showed that the researched institution behaves in a non-critical manner towards the proposed reforms, incorporating the general guidelines defined by the reforms into internal documents and, even in what could be different, such as the organization of course workloads, preferred to follow the official recommendation and reduce the workload of the subjects that make up the BNCC. The analysis of the interviews allowed us to verify that although teachers want to, they are unable to participate and interfere more intensely in this process, which compromises their understanding of it. The perception that remains is that the level of understanding about the reforms is determined by the impact it produces on daily work, as among the teachers interviewed, the changes had no impact on the workload of their subjects, they were limited to criticisms about the reduction of the course load of BNCC subjects, without mentioning the conception of education, training, comprehensive education, the relationship between work and education, the political process of elaborating the reforms and their agents. As a result, the perception they express about the process is filtered by the way in which the CPS documents incorporated the reforms.